Transurethral vaportrode electrovaporization of the prostate: Physical principles, technique, and results - Narayan, Perinchery; Tewari, Ashutosh; Garzotto, Mark; Parramore, Herman W.; Schalow, Erica; Starling, Jeff; Jones, Talmadge (Urology (Ridgewood, N.J.), 1996)
Abstract This is a study to evaluate technique, efficacy, and safety of a new electrosurgical instrument (Vaportrode) in management of benign prostatic hyperplasia (BPH). Forty-two symptomatic BPH patients form the subject of this study. Preoperative and postoperative International Prostate Symptom Score (IPSS), peak flow rates (PFR), postvoid residual urine (PVR), operative details, and complications were recorded in each patient. Baseline, 1, 3, and 6 months follow-up data were used for analyses. Results reveal that transurethral electrovaporization of the prostate (TUEVP) is a reasonable procedure to treat symptomatic BPH, and at 6 months, this procedure results in 68% reduction in IPSS, 128% improvement in PFR, and 58% reduction in PVR. Even in patients who are in retention prior to TUEVP, at 6 months the IPSS is 7.7, PFR is 20.4 cc/s, and PVR reduces to 130 cc. The procedure is well tolerated without any significant short-term complications. The results of this modality in improving the symptoms and PFR in symptomatic BPH patients in the short term appear promising. Advantages over transurethral resection (TUR) of the prostate and laser prostatectomy include familiarity of the transurethral route, lack of need for high-cost laser equipment and fibers, excellent intraoperative hemostasis, lack of bleeding or fluid absorption, and ability to cause a predictable TUR-like prostate defect at the end of the procedure. Further studies involving larger numbers of patients and longer follow-up are warranted to assess further the utility of this procedure.